Tsunami resonance and standing waves in the South China Sea. (15th October 2022) - Ren, Zhiyuan; Liu, Hua; Jimenez, Cesar; Wang, Yuchen
Abstract: This study investigated tsunami resonance and multiscale standing waves induced by a hypothetical extreme tsunami in the South China Sea (SCS). The nonlinear shallow water equation model was adopted to calculate the tsunami propagation from an Mw 9.3 earthquake occurring in the Manila Trench. Then, the sea surface elevation 24 h following the earthquake was computed for spectral analysis to characterize edge and standing waves for the explanation of tsunami oscillations in the semi-enclosed marginal sea. The spectra of background noise at eight tide gauges were calculated and used as a reference. Results showed that standing waves between 29 and 256 min were the dominant wave modes in the entire SCS. The resonance characteristics around Hainan Island and Lingding Bay were also investigated. Spectral analysis at different spatial scales indicated wave trapping and tsunami resonance over the continental shelf and along the coast. The tsunami resonance modes induced by the hypothetical extreme tsunami reveal information regarding energy concentrations and long-lasting tsunamis in the coastal region and provide a novel perspective for identifying at-risk regions in tsunami hazard assessment. Highlights: Tsunami resonance behavior from an Mw 9.3 earthquake was investigated. Oscillation modes had dominant periods of 29–256 min in the South China Sea. Resonance characteristics were studied in three different spatial scales. Standing waves were identified on the continental shelf and along the coast.